2018
DOI: 10.1038/s41467-018-05290-6
|View full text |Cite
|
Sign up to set email alerts
|

Horse Y chromosome assembly displays unique evolutionary features and putative stallion fertility genes

Abstract: Dynamic evolutionary processes and complex structure make the Y chromosome among the most diverse and least understood regions in mammalian genomes. Here, we present an annotated assembly of the male specific region of the horse Y chromosome (eMSY), representing the first comprehensive Y assembly in odd-toed ungulates. The eMSY comprises single-copy, equine specific multi-copy, PAR transposed, and novel ampliconic sequence classes. The eMSY gene density approaches that of autosomes with the highest number of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
107
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(111 citation statements)
references
References 69 publications
(162 reference statements)
3
107
0
1
Order By: Relevance
“…We observed strong testis-biased expression among genes that had 530 duplicated and translocated to the Y chromosome, similar to patterns observed on other Y 531 chromosomes (Carvalho et al 2000;Skaletsky et al 2003;Murphy et al 2006;Hughes et 532 al. 2010;Paria et al 2011;Soh et al 2014;Mahajan and Bachtrog 2017;Janečka et al 2018).…”
mentioning
confidence: 99%
“…We observed strong testis-biased expression among genes that had 530 duplicated and translocated to the Y chromosome, similar to patterns observed on other Y 531 chromosomes (Carvalho et al 2000;Skaletsky et al 2003;Murphy et al 2006;Hughes et 532 al. 2010;Paria et al 2011;Soh et al 2014;Mahajan and Bachtrog 2017;Janečka et al 2018).…”
mentioning
confidence: 99%
“…The cattle X-d2b region contains SRY and is in a telomeric position similar to the X-d2 region of pig. The cattle X-d2b region contains two copies of RBMY, which is also duplicated in the horse X-d2 [20].…”
Section: Comparison Of X-degenerate Y Chromosome Regionsmentioning
confidence: 99%
“…A study of bovine Y chromosome gene expression has contributed information on genes in X-d regions [16], but interpretation of the data is limited by the relatively poor quality of the available Y chromosome assembly. [18], pig [19] and horse [20], 84 have well characterised and assembled Y chromosomes. 85…”
mentioning
confidence: 99%
“…The timing of this bottleneck is not clear, however, as aDNA studies have revealed that ancient domestic horses had greater Y-chromosome diversity than modern horses (Lippold et al 2011a;Librado et al 2017). The recent publication of the first complete assembly of the horse Y-chromosome should assist in future aDNA studies of male-biased processes in horse domestication (Janečka et al 2018).…”
Section: Horsesmentioning
confidence: 99%